Hierarchical structures of anodised cold gas sprayed titanium coatings. (4th March 2018) - Vilardell, A. M.; Cinca, N.; Pacheco, I.; Santiveri, C.; Dosta, S.; Cano, I. G.; Guilemany, J. M.; Sarret, M.; Muller, C.
ABSTRACT: Cold gas spray (CGS) titanium coatings have been produced to obtain porous and rough coatings with enhanced mechanical performance. The coatings from optimal spraying conditions reached tensile strength values up to 40 MPa, shear strength up to 39 MPa and a loss mass of 37 mg/100 cycles in abrasive testing, values in accordance with the ASTM standards to be applied for orthopaedic joint prostheses. An innovative hierarchical structure (micro-nano) consisted of a TiO2 nanotubes top layer obtained by anodisation onto a CGS Ti coating. The present paper focuses on the characterisation of both surfaces, as-sprayed CGS Ti layer and double Ti-TiO2 layer, in terms of mechanical properties, surface topography and wettability (contact angle). There were not significant changes in micro-roughness, Ra∼40 µm and Ra∼30 µm, but a significant decrease in contact angle, from ≈26° up to 0°, was observed between these two structures. This behaviour indicates that the combination of the CGS + anodising results in promising high roughness superhydrophilic surfaces, ideal for biomedical applications.